Uptake of prostate-specific membrane antigen-targeted 18F-DCFPyL in avascular necrosis of the femoral head - Torga, Gonzalo; Yin, Yafu; Pomper, Martin G.; Pienta, Kenneth J.; Gorin, Michael A.; Rowe, Steven P. (World Journal of Nuclear Medicine, 2019)
In recent years, the emergence of prostate-specific membrane antigen (PSMA)-targeted positron-emission tomography (PET) imaging has brought about a paradigm shift in the way that prostate cancer (PCa) is imaged in many parts of the world. Although PSMA-targeted PET imaging has been demonstrated to be a highly sensitive and specific imaging modality for the identification of sites of PCa, its clinical utility hinges on the ability of imaging specialists and their clinical colleagues to recognize potential false-positive sources of uptake and to tailor therapy based on that recognition. In this manuscript, we report the case of a 74-year-old male with a history of recurrent PCa who was referred for a restaging PSMA-targeted 18F-DCFPyL PET/computed tomography (PET/CT). PET images demonstrated low level but focal and definitive uptake in the left femoral head. This uptake corresponded to sclerotic changes on CT whose morphology was most compatible with avascular necrosis without femoral head collapse. In the presented case, the integrated assessment of the CT imaging together with the PET findings was fundamental to avoid misinterpretation of the left femur finding as metastatic disease, which would have ultimately altered the clinical management of the patient.
Keywords: 18F-DCFPyL; avascular necrosis; positron-emission tomography/computed tomography; prostate cancer; prostate-specific membrane antigen